Sex and age differences in the Multiple Sclerosis prodrome - Yusuf, Fardowsa L. A.; Wijnands, José M. A.; Karim, Mohammad Ehsanul; Kingwell, Elaine; Zhu, Feng; Evans, Charity; Fisk, John D.; Zhao, Yinshan; Marrie, Ruth Ann; Tremlett, Helen (Frontiers in Neurology, 2022)
Background and objectives Little is known of the potential sex and age differences in the MS prodrome. We investigated sex and age differences in healthcare utilization during the MS prodrome. Methods This was a population-based matched cohort study linking administrative and clinical data from British Columbia, Canada (population = 5 million). MS cases in the 5 years preceding a first demyelinating event (“administrative cohort;” n = 6,863) or MS symptom onset (“clinical cohort;” n = 966) were compared to age-, sex- and geographically-matched controls (n = 31,865/4,534). Negative binomial and modified Poisson models were used to compare the rates of physician visits and hospitalizations per international classification of diseases chapter, and prescriptions filled per drug class, between MS cases and controls across sex and age-groups (< 30, 30–49, ≥50 years). Results In the administrative cohort, males with MS had a higher relative rate for genitourinary-related visits (males: adjusted Rate Ratio (aRR) = 1.65, females: aRR = 1.19, likelihood ratio test P = 0.02) and antivertigo prescriptions (males: aRR = 4.72, females: aRR = 3.01 P < 0.01). Injury and infection-related hospitalizations were relatively more frequent for ≥50-year-olds (injuries < 30/30–49/≥50: aRR = 1.16/1.39/2.12, P < 0.01; infections 30–49/≥50: aRR = 1.43/2.72, P = 0.03), while sensory-related visits and cardiovascular prescriptions were relatively more common in younger persons (sensory 30–49/≥50: aRR = 1.67/1.45, P = 0.03; cardiovascular < 30/30–49/≥50: aRR = 1.56/1.39/1.18, P < 0.01). General practitioner visits were relatively more frequent in males (males: aRR = 1.63, females: aRR = 1.40, P < 0.01) and ≥50-year-olds (< 30/≥50: aRR = 1.32/1.55, P = 0.02), while differences in ophthalmologist visits were disproportionally larger among younger persons, < 50-years-old (< 30/30–49/≥50: aRR = 2.25/2.20/1.55, P < 0.01). None of the sex and age-related differences in the smaller clinical cohort reached significance (P ≥ 0.05). Discussion Sex and age-specific differences in healthcare use were observed in the 5 years before MS onset. Findings demonstrate fundamental heterogeneity in the MS prodromal presentation.